2012
DOI: 10.5539/ijbm.v7n5p100
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the Impact of Gender Differences on Organizational Commitment: Empirical Evidence from a Private SME in Iran

Abstract: Employee commitment is one of the most important elements that help organizations to achieve their goals. This study investigates the impact of gender differences on organizational commitment.108 employees of a private small and medium enterprise (SME) company in Iran are randomly selected for this study. The organizational commitment instrument used in this research is adopted from the Allen and Meyer (1990) scale. Based on this scale, three organizational factors (affective commitment, continuance commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 56 publications
4
21
2
Order By: Relevance
“…Results of the present study showed that there was no statistically significant relationship between nurses’ employment status and their organizational commitment and its dimensions. Results of the present study were consistent with the results obtained in Khalili’s study (33). …”
Section: Discussionsupporting
confidence: 93%
“…Results of the present study showed that there was no statistically significant relationship between nurses’ employment status and their organizational commitment and its dimensions. Results of the present study were consistent with the results obtained in Khalili’s study (33). …”
Section: Discussionsupporting
confidence: 93%
“…This implies that it is important for managers to focus on improving the communication satisfaction level of male employees which in turn will increase organizational commitment level. This finding is confirmed by Clayton, Petzall, Lynch and Margaret (2007) and Khalili and Asmawi (2012), who found that female tend to have higher organizational commitment than male.…”
Section: Discussionsupporting
confidence: 67%
“…The commitment of employees to their places of work is of considerable interest for the existence and success of many organizations (Yavuz, 2010) and is one of the most important elements that help organizations achieve their goals (Khalili and Asmawi, 2012). It is at the heart of human resource management (Gbadamosi et al, 2007) and has resulted in research with a strong focus on how organizations can improve the organizational commitment of their employees (Newman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%